2018
DOI: 10.3389/fpls.2018.00170
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidences of Biofortification with Iodine of “Carota di Polignano”, An Italian Carrot Landrace

Abstract: The “Carota di Polignano” (Polignano Carrot – PC, Daucus carota L.) is a multi-colored landrace, cultivated in the Southern Italy, whose colors range from yellow to purple. Iodine is an essential micronutrient for humans, since it is a key component of thyroid hormones, which regulate the growth and development of the human body. The main source for iodine assumption is represented by diet, but its concentration in the vegetables is usually limited with respect to human needs. To this purpose, two experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
1
31
1
1
Order By: Relevance
“…A novel challenge in agriculture is the production of tailored foods, i.e., foods specifically suitable for target groups of people with particular nutritional needs. In fact, in recent years, a number of studies have highlighted the possibility of producing vegetables for specific physiological conditions, such as biofortified vegetables, with the aim of counteracting different nutritional deficits [1][2][3][4][5][6][7][8]. In general, these authors reported evidence on the use of specific growing protocols aimed to increase the content of specific nutrients in plant tissues, such as iodine (I), silicon (Si), calcium (Ca), selenium (Se), zinc (Zn), and iron (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…A novel challenge in agriculture is the production of tailored foods, i.e., foods specifically suitable for target groups of people with particular nutritional needs. In fact, in recent years, a number of studies have highlighted the possibility of producing vegetables for specific physiological conditions, such as biofortified vegetables, with the aim of counteracting different nutritional deficits [1][2][3][4][5][6][7][8]. In general, these authors reported evidence on the use of specific growing protocols aimed to increase the content of specific nutrients in plant tissues, such as iodine (I), silicon (Si), calcium (Ca), selenium (Se), zinc (Zn), and iron (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…Several Apulian varieties are included in the list of vegetables at risk of genetic erosion [9], which constitutes an issue for the loss of the genetic traits important for the biodiversity and nutritional quality of the varieties [8][9][10]. In the Apulia region, three main ecotypes of colored carrots have been reported, whose names are strictly related to the production areas: Polignano (province of Bari, [11]), Zapponeta, (province of Foggia), and Tiggiano (which also includes Tricase and Specchia villages, in the province of Lecce [12]). Tiggiano carrot cultivation is strongly related to the popular cult of the Saint Ippazio, protector of male virility.…”
Section: Introductionmentioning
confidence: 99%
“…These, in turn, can affect the properties of foodstuffs, its durability and stability [17]. There is also a risk that the concentrations of the substance introduced into the fortified foodstuff will be too high or even potentially harmful [14].…”
Section: Agronomic Biofortification As the Key To Enrichment Of Plantmentioning
confidence: 99%
“…They show considerable homology to methyltransferases involved in responses to salinity or glucosinolate metabolism, suggesting that methyl iodide production may be a defence mechanism in plants [28]. Literature research indicates that there is no single pattern according to which chemical forms of iodine affect plants [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Each species will react in a different way, depending on the method of cultivation and application of iodine.…”
Section: Chemical Forms Of Iodine Used For Biofortification Of Crop Pmentioning
confidence: 99%
See 1 more Smart Citation